Repurposing isoxazoline veterinary drugs for control of vector-borne human diseases - Miglianico, Marie; Eldering, Maarten; Slater, Hannah; Ferguson, Neil; Ambrose, Pauline; Lees, Rosemary S; Koolen, Karin M J; Pruzinova, Katerina; Jancarova, Magdalena; Volf, Petr; Koenraadt, Constantianus J M; Duerr, Hans-Peter; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Isoxazolines are oral insecticidal drugs currently licensed for ectoparasite control in companion animals. Here we propose their use in humans for the reduction of vector-borne disease incidence. Fluralaner and afoxolaner rapidly killed Anopheles, Aedes, and Culex mosquitoes and Phlebotomus sand flies after feeding on a drug-supplemented blood meal, with IC50 values ranging from 33 to 575 nM, and were fully active against strains with preexisting resistance to common insecticides. Based on allometric scaling of preclinical pharmacokinetics data, we predict that a single human median dose of 260 mg (IQR, 177-407 mg) for afoxolaner, or 410 mg (IQR, 278-648 mg) for fluralaner, could provide an insecticidal effect lasting 50-90 days against mosquitoes and Phlebotomus sand flies. Computational modeling showed that seasonal mass drug administration of such a single dose to a fraction of a regional population would dramatically reduce clinical cases of Zika and malaria in endemic settings. Isoxazolines therefore represent a promising new component of drug-based vector control.
Keywords: moskyti - kontrola; isoxazoline; Culicidae; Animals; Humans; insecticide; Mosquito Control; kontrola infekčních nemocí; vector control; Insecticides; komáří přenašeči; zika fever; zvířata; insekticidy; Psychodidae; malaria; Mosquito Vectors; lidé; Communicable Disease Control